The Role of Nutritional Status on Polypharmacy, Cognition, and Functional Capacity of Institutionalized Elderly: A Systematic Review - Caçador, Catarina (2022)
Adequate nutritional status is necessary for the proper management of polypharmacy, the prevention of cognitive decline, and the maintenance of functional capacity in activities of daily living. Although several studies validate this fact for the general elderly population, data on institutionalized seniors concerning this relation are scarce. A systematic review was performed according to the PRISMA guidelines, aiming to study the potential correlation between nutritional status and polypharmacy, cognitive decline, and functional performance in institutionalized elders. The search was limited to studies in English or Portuguese in the last decade. Inclusion criteria relied on the PICO method. Five studies explored the relationship of nutritional status with cognitive performance in the institutionalized elderly, and nine prospective observational studies reported significant positive associations between appropriate nutritional status and physical abilities. Nutritional status was primarily measured by MNA. Adequate nutritional status was described as an important parameter in preventing cognitive and functional decline in the institutionalized elderly. No studies were found describing the impact of nutritional status on the prevention of polypharmacy. Given the strong impact of malnutrition found in the studies in cognition and functional abilities in the institutionalized elderly, an evaluation of nutritional status of the elders is crucial to prevent health problems and allow early intervention programs in order to further prevent health decline